PENGARUH MOTIVASI KERJA DAN KOMUNIKASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT TALIABU BARAT LAUT KABUPATEN PULAU TALIABU - Samiu, La Diu; Saudin, La (Yayasan Education and Social Center, 2024)
This study aims to determine the partial and simultaneous effects of Work Motivation and Work Communication on Employee Performance at the Taliabu Barat Laut District Office, Pulau Taliabu Regency. A sample of 25 employees from the office was selected using purposive sampling. Data was collected through interviews and questionnaires and analyzed using descriptive quantitative methods, including frequency tables and multiple linear regression. The data was processed using SPSS version 25.0. The results of the t-test indicated that both Work Motivation (X1) and Work Communication (X2) had a partial positive and significant effect on Employee Performance (Y). The ANOVA (Analysis of Variance) test yielded an F-count of 156.760, which was significantly greater than the F-table value of 3.44 (F-count > F-table). This indicates that both Work Motivation and Work Communication simultaneously have a positive and significant effect on Employee Performance. Partially, Work Communication emerged as the most dominant variable with a coefficient value of 0.976, suggesting that it has the greatest influence on Employee Performance (Y).